La necesidad de incorporar en el Código De Trabajo Ecuatoriano, disposiciones que garanticen de manera más efectiva y eficiente la vigencia del derecho a la seguridad jurídica y a la salud de los Trabajadores Ecuatorianos - Peralta Rodíguez, Esteban Daniel (2015)
The Ecuadorian government through the provision contained in paragraph 5 of Article 326 of the Constitution of the Republic of Ecuador, enshrined as one of the principles underpinning the right to work in our country, that all persons are entitled to develop their activities in a proper and conducive environment that ensures their health, integrity, health and welfare. So one of the basic guarantees for the performance of work by workers, job security and health. In order to properly develop the legal framework to ensure compliance with these guarantees, has built a regulatory regime that is in force in the Labour Code provisions that ratify the duty of employers to comply with the requirements necessary to facilitate the existence appropriate and conducive environment that speaks the constitutional rule indicated above. Despite the existence of constitutional and legal norms, quite explicit about the duty of employers to ensure worker safety and health of workers, while making the performance of the activity for which they were hired, in Ecuador the failure persists of this legislation with very few public and private companies and employers, who have incorporated within their productive activity, which must be done in accordance with those rules. One of the reasons for non-compliance continues regarding standards of workplace safety and health of workers, is that the provisions of the Labour Code, are not strong enough as to coercion is concerned, there is generated a kind of impunity, which result in more severe, constant exposure of workers to risks that harm their personal integrity and even threaten the lives of those people. The problems described in the above lines is studied in this research paper, and has been developed according to the rules laid down in Regulation Regime Academic National University of Loja. Being proactive oriented research, this paper concludes with the presentation of a legal proposal for reform of the Labour Code, designed to incorporate legal provisions to ensure effective and efficient implementation of all constitutional and legal norms that are related to security labor and health of workers